2020
DOI: 10.1093/cid/ciaa380
|View full text |Cite
|
Sign up to set email alerts
|

CRF01_AE and CRF01_AE Cluster 4 Are Associated With Poor Immune Recovery in Chinese Patients Under Combination Antiretroviral Therapy

Abstract: Background HIV-1 clades and clusters have different epidemic patterns and phenotypic profiles. It is unclear if they also affect patient’s immune recovery (IR) in combined antiretroviral therapy (cART). Methods We conducted cohort study on 853 patients under cART for evaluating the impacts of viral factor on host IR. We used Generalized Estimating Equations for factor affecting CD4 recovery, Kaplan–Meier curves for the probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Previous studies have shown that there is no significant difference in immune recovery between CRF01_AE and B strains in a combined ART cohort 32 . Recently, researchers found that compared to that with CRF07_BC, CRF01_AE is associated with a lower CD4+ cell count recovery and a slower rate of immune recovery in combined ART 33 . Our study is the first to show that there is no difference in the therapeutic efficacy of combined ART among patients with CRF01_AE, CRF07_BC, CRF08_BC, and other genotypes, using death as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is no significant difference in immune recovery between CRF01_AE and B strains in a combined ART cohort 32 . Recently, researchers found that compared to that with CRF07_BC, CRF01_AE is associated with a lower CD4+ cell count recovery and a slower rate of immune recovery in combined ART 33 . Our study is the first to show that there is no difference in the therapeutic efficacy of combined ART among patients with CRF01_AE, CRF07_BC, CRF08_BC, and other genotypes, using death as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the significant difference in IR ability among the HIV patients with different genotypes could be attributed to the high proportion of X4 tropism in the CRF01_AE subtype and its cluster 1. Although this study was based on the viral tropism obtained by HIV-1 genotyping prediction, its accuracy has been verified by previous research in the same category [ 28 , 45 ].…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, in the N-linked glycan site at the beginning of the V3 loop (V3 positions 6–8, HXB2 nos.301–303), the CRF01_AE cluster 1 and 2 sequences had lost the residue N/T at positions 7–8 site, which was replaced by Lysine and Isoleucine amino acids. Previous studies have shown that the preference for the CXCR4 co-receptor tropism was positively correlated with the K7, R11, R13 and K32 (HXB2 numbers K302, R306, R308 and K327) amino acid substitutions of V3 loop [ 18 , 45 ]. Therefore, this reveals a greater propensity to X4-using in CRF01_AE and its cluster 1.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CRF07_BC has a lower TDR prevalence than subtype B and CRF01_AE (1.5% vs. 4.8% vs. 5.6%) respectively 27 , 28 . Ge et al 29 and Cao et al 30 have demonstrated that CRF07_BC is associated with better immune recovery in Chinese patients undergoing antiretroviral treatment (ART) compared to that of patients infected with CRF01_AE. Taken together, these results support the hypothesis that CRF07_BC is less pathogenic than subtype B.…”
Section: Discussionmentioning
confidence: 99%